Criticality analysis of defects in civil engineering structures: Case of onshore process plant - Hammad, D.B. (Elsevier Ltd, 2014)
In order to address maintenance need of specific structures, a criticality analysis of the structures is essential. This paper presents an analysis of experts' judgment using Analytic Hierarchy Process (AHP). Four criteria; people, assets, environment and reputation were considered as criteria. Sample representatives of Ten (10) civil engineering structures from onshore process plant were treated as alternatives. The judgment of the criteria with respect to the main goal was consistent with consistency value of 0.03. Control building (CB) was considered to be the most critical among the selected structure. Although, the technique is based on subjective experts' judgment, but is considered very important in designing maintenance plan for existing structures where design data is not available. Â© 2014 The Authors. Published by Elsevier Ltd.